War Through the Ages - Montross, Lynn, 1895-1961 (GHQ, Rawalpindi Army Education Press, 1986)
"This book is unique -- the stirring story of war in all its phases from 490 B.C. to our own day. Since its first appearance fifteen years ago it has become a classic, a storehouse of military lore for the specialist and layman alike. The present edition is thoroughly revised and greatly enlarged. The World War II chapter have been rewritten to make use of sources not available earlier, particularly German and Japanese documents and memoirs. Completely new material has been added, covering more recent events such as the cold war between the Communist states and Western nations, the shooting war in Korea, and the Lebanon intervention.
Include Picture and Index
Keywords: Military Art and Science -- History -- Military History -- Military Art and Science